Planning the main production tables using the correct binary programming method - بخيت, عبد الجبار خضر (Journal of Economics and Administrative Sciences, 2010)
This research include building mathematical models for aggregating planning and shorting planning by using integer programming technique for planning master production scheduling in order to control on the operating production for manufacturing companies to achieve their objectives of increasing the efficiency of utilizing resources and reduce storage and  improving customers service  through  deliver in the actual dates and reducing delays.